1997
DOI: 10.1017/s1037291100001205
|View full text |Cite
|
Sign up to set email alerts
|

Taking charge of the future. From states of anxiety and dependence to becoming actualised professionals

Abstract: Between the mid 1940's and the mid 1980's psychology, guidance and counselling services were established and rapidly expanded within Australian state departments of education. This occurred in a socio-political context where the values of social justice and concern for the disadvantaged were regarded as important by communities looking to governments to reflect these values through appropriate policies and programs. Since then a distinct change has occurred. Economic Rationalism and the move to greater school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Our existence as a profession will to a great extent depend on our ability to contribute positively to a needed discussion about the main social questions in our society as they are seen today, (p.8) Similarly, in a review of a number of innovative school psychology services programs from different states across the U.S., Franklin (1995) concluded that school psychology services are increasingly being asked to re-examine their roles, functions and skills, and need to resist the temptation to remain locked into models of delivery that are 'comfortable.' This view is shared by Drent and Murphy (1997) in their paper on recent developments in Australian school psychology. Oakland (1996) who has been researching patterns of school psychology internationally for the last two decades offers three meta-strategies for ensuring a viable future for school psychology into the 21st century : firstly, the need to find ways of aligning ourselves with all of education not just with special education, secondly, the need to actively promote the health of 'community', and thirdly, the ability to be able to use well the basic building blocks of child development.…”
Section: Organisational Change and School Psychology : The Present Mo...mentioning
confidence: 90%
See 1 more Smart Citation
“…Our existence as a profession will to a great extent depend on our ability to contribute positively to a needed discussion about the main social questions in our society as they are seen today, (p.8) Similarly, in a review of a number of innovative school psychology services programs from different states across the U.S., Franklin (1995) concluded that school psychology services are increasingly being asked to re-examine their roles, functions and skills, and need to resist the temptation to remain locked into models of delivery that are 'comfortable.' This view is shared by Drent and Murphy (1997) in their paper on recent developments in Australian school psychology. Oakland (1996) who has been researching patterns of school psychology internationally for the last two decades offers three meta-strategies for ensuring a viable future for school psychology into the 21st century : firstly, the need to find ways of aligning ourselves with all of education not just with special education, secondly, the need to actively promote the health of 'community', and thirdly, the ability to be able to use well the basic building blocks of child development.…”
Section: Organisational Change and School Psychology : The Present Mo...mentioning
confidence: 90%
“…This approach has value for helping professionals employed within public sector organisations. While we are typically employed to undertake certain functions, it is essential for our professional and personal health that we find ways to pursue themes or strands of experience that provide both work satisfaction and professional growth ( Drent and Murphy, 1997) . In his best seller, Covey (1992) distinguishes between areas of concerns and the areas of influence in our lives.…”
Section: (B) Valuesmentioning
confidence: 99%